If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 = 3w + 3(w + -7) Reorder the terms: 3 = 3w + 3(-7 + w) 3 = 3w + (-7 * 3 + w * 3) 3 = 3w + (-21 + 3w) Reorder the terms: 3 = -21 + 3w + 3w Combine like terms: 3w + 3w = 6w 3 = -21 + 6w Solving 3 = -21 + 6w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-6w' to each side of the equation. 3 + -6w = -21 + 6w + -6w Combine like terms: 6w + -6w = 0 3 + -6w = -21 + 0 3 + -6w = -21 Add '-3' to each side of the equation. 3 + -3 + -6w = -21 + -3 Combine like terms: 3 + -3 = 0 0 + -6w = -21 + -3 -6w = -21 + -3 Combine like terms: -21 + -3 = -24 -6w = -24 Divide each side by '-6'. w = 4 Simplifying w = 4
| 5=6n-1 | | x*x+5x+11=-2x+5 | | 0.5x+2=6 | | 5q+29=14 | | x*x-3x+6=10 | | 2+3m=-22 | | -5u+3=-4u | | -4(w-4)=-9w+6 | | 3u+7(u+2)=-16 | | 1.33x-5=23 | | xsquared=8 | | -3r-14=-4-5r | | 121x= | | -0.25x-19=1 | | 4(c-6)=(c+2) | | 5h-14=16+4h | | 50+3y=-7y | | 2x+6-7x=21 | | x*x-4x-32=0 | | 17x+3=139 | | 22(2-d)+9=198 | | -2y=3x+10 | | 33x+2880= | | 5+3(s-3t)=0 | | 6p-4=12p+8 | | Df+10=3ford | | 2(n+2)=-11 | | 3(x-5)-8=1-(1x-4) | | -12=6p | | 6p=12p+12 | | 2(2x+3)=-4+2(2x+5) | | 8+5(x+3)+7x= |